2018
DOI: 10.1002/hep.29645
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis by caspase11/4‐gasdermin‐D pathway in alcoholic hepatitis in mice and patients

Abstract: These results implicate pyroptosis induced by the CASP11/4-GSDMD pathway in the pathogenesis of AH. (Hepatology 2018;67:1737-1753).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
171
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(179 citation statements)
references
References 44 publications
(94 reference statements)
7
171
1
Order By: Relevance
“…Cirrhotic liver tissues from different etiologies (e.g., NASH, hepatitis C virus [HCV], autoimmune hepatitis [AH]) and liver tissues from acetaminophen (APAP)–induced liver failure were obtained through the Liver Tissue Procurement and Distribution System (National Institutes of Health contract HHSN276201200017C), University of Minnesota. Severe alcoholic hepatitis (SAH) patient and control human livers were obtained from the Clinical Resources for Alcoholic Hepatitis (1R24AA025017), Johns Hopkins University, as described . All samples were collected by snap‐freezing in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Cirrhotic liver tissues from different etiologies (e.g., NASH, hepatitis C virus [HCV], autoimmune hepatitis [AH]) and liver tissues from acetaminophen (APAP)–induced liver failure were obtained through the Liver Tissue Procurement and Distribution System (National Institutes of Health contract HHSN276201200017C), University of Minnesota. Severe alcoholic hepatitis (SAH) patient and control human livers were obtained from the Clinical Resources for Alcoholic Hepatitis (1R24AA025017), Johns Hopkins University, as described . All samples were collected by snap‐freezing in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 76%
“…Severe alcoholic hepatitis (SAH) patient and control human livers were obtained from the Clinical Resources for Alcoholic Hepatitis (1R24AA025017), Johns Hopkins University, as described. (25) All samples were collected by snap-freezing in liquid nitrogen.…”
Section: Human Liver Samplesmentioning
confidence: 99%
“…124 A previous study demonstrated that the caspase-11/4-GSDMD pathway was activated in the liver during alcoholic hepatitis. 125 In a mouse model of alcoholic hepatitis, a caspase-11 deficiency abolished the ductular reaction, hepatocellular death, and liver bacterial load, which implies that caspase-11 contributes to the pathogenesis of alcoholic liver disease. By contrast, GSDMD may protect against noninfectious liver injury, which is induced by hemorrhagic shock associated with resuscitation or acetaminophen overdose, by regulating apoptosis and necroptosis.…”
Section: Inflammasome-related Diseasesmentioning
confidence: 98%
“…GSDMD also contributes to sterile inflammation in liver disease (Khanova et al, 2018; Xu et al, 2018). In a mouse model of alcoholic hepatitis, it was shown that GSDMD and caspase-11 were both activated and that expression of constitutively active GSDMD worsened hepatocellular death and leukocyte inflammation (Khanova et al, 2018).…”
Section: Gsdmd and Control Of Sterile And Nonsterile Inflammationmentioning
confidence: 99%
“…GSDMD also contributes to sterile inflammation in liver disease (Khanova et al, 2018; Xu et al, 2018). In a mouse model of alcoholic hepatitis, it was shown that GSDMD and caspase-11 were both activated and that expression of constitutively active GSDMD worsened hepatocellular death and leukocyte inflammation (Khanova et al, 2018). Similarly, samples from nonalcoholic steatohepatitis patients displayed GSDMD-driven pyroptosis and GSDMD deletion–mitigated development of steatohepatitis in mice (Xu et al, 2018).…”
Section: Gsdmd and Control Of Sterile And Nonsterile Inflammationmentioning
confidence: 99%